Cerebral palsy: effects of twinning, birthweight, and gestational age. Issue 3 (November 1996) - Williams, K; Hennessy, E; Alberman, E
Abstract : AIMS: To determine the effects of birthweight and gestational age on the risk of cerebral palsy for multiple and singleton births. METHODS: Children on the North East Thames Regional Health Authority Interactive Child Health System, born between 1 January 1980 and 31 December 1986, and notified as having cerebral palsy, were included. Cases of postneonatal onset, of known progressive, or non-cerebral pathology and with only mild signs were excluded. Rates and relative risks were calculated using the most complete data, which related to 1985-86, and comprised 102, 059 singletons and 2367 twins. Logistic regression was used to examine the associations between being a twin, gestational age, and birthweight. RESULTS: The crude rate per 1000 survivors at 1 year of age was 1.0 in singletons and 7.4 in twins. The relative risk was greatest in twins weighing more than 2499 g (4.5). However, after adjusting for reduced birthweight of twins it was the relative risk of twins weighing less than 1400 g that was significantly increased. Logistic regression confirmed that lower fetal growth, lower gestational age, and being a twin are all independent risk factors for cerebral palsy. CONCLUSION: The increased risk to twins of cerebral palsy is not entirely explained by their increased risk of prematurity and low birthweight.